Immunomodulatory activity of exopolysaccharide producing Leuconostoc citreum strain isolated from Pico cheese. (June 2017) - Domingos-Lopes, M.F.P.; Nagy, A.; Stanton, C.; Ross, P.R.; Gelencsér, E.; Silva, C.C.G.
Highlights: EPS-producer Leu. citreum L3C1E7 strain was tested for immunomodulatory action. Leu. citreum L3C1E7 reduced IL-8 release by LPS-induced HT-29 cells. Orally administered live strain modulate the systemic immune response in rats. The strain down-regulated the over-production of IgE, in a rat-induced asthma model. Abstract: The present study aimed to assess the immunomodulatory properties of Leuconostoc citreum L3C1E7, isolated from Pico cheese. In vitro tests showed a significant (P < 0.05) effect of live strain on reducing pro-inflammatory cytokine IL-8 secretion by lipopolysaccharide-induced HT-29 cells. The probiotic activity of the strain was further investigated in two rat models. Rats fed with ovalbumin (OVA), with/without the strain, were vaccinated subcutaneously with OVA on day 7 and 14. Allergen-specific IgG1 and IgG2a responses were restored after pre-feeding the strain. In a second experiment, an OVA-induced asthma model was used. Plasma levels of allergen-specific IgG1 and IgG2a were significantly (P < 0.05) raised in the OVA-fed group, while co-feeding with the strain significantly (P < 0.05) reduced plasma levels of these antibodies. Moreover, plasma OVA-specific IgE was significantly (P < 0.05) reduced by feeding the strain. These data show that feeding Leu. citreum L3C1E7 suppresses allergen-specific IgE synthesis and may alleviate Th2-mediated allergic symptoms.